2021
DOI: 10.1007/s12013-021-01019-3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Research on Bladder Cancer Targeting Peptides: a Review

Abstract: Bladder cancer (Bca) is the second most common malignant tumor of the genitourinary system in Chinese male population with high potential of recurrence and progression. The overall prognosis has not been improved significantly for the past 30 years due to the lack of early theranostic technique. Currently the early theranostic technique for bladder cancer is mainly through the intravesical approach, but the clinical outcomes are poor due to the limited tumor-targeting efficiency. Therefore, the targeting pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Overall, urinary peptides resulted in AUC values comparable to or greater than those observed for other urinary PCa biomarkers based on RNA, DNA or proteins (8,17). Our sample preparation protocol is simplest, cheapest and fastest when compared to experimental approaches traditionally used in the isolation of urinary protein/peptide biomarkers for LC-MS analysis (6,(18)(19)(20)(21)(22)(23). We analyzed naturally occurring urinary peptides and, therefore, our protocol did not include an enzymatic protein digestion step (e.g., trypsin digestion).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Overall, urinary peptides resulted in AUC values comparable to or greater than those observed for other urinary PCa biomarkers based on RNA, DNA or proteins (8,17). Our sample preparation protocol is simplest, cheapest and fastest when compared to experimental approaches traditionally used in the isolation of urinary protein/peptide biomarkers for LC-MS analysis (6,(18)(19)(20)(21)(22)(23). We analyzed naturally occurring urinary peptides and, therefore, our protocol did not include an enzymatic protein digestion step (e.g., trypsin digestion).…”
Section: Discussionmentioning
confidence: 81%
“…Our sample preparation protocol is simplest, cheapest and fastest when compared to experimental approaches traditionally used in the isolation of urinary protein/peptide biomarkers for LC-MS analysis ( 6 , 18 23 ). We analyzed naturally occurring urinary peptides and, therefore, our protocol did not include an enzymatic protein digestion step (e.g., trypsin digestion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 About 80% of BCa patients have reduced symptoms after intravesical chemotherapy, but the specificity of this method is not high. 10 At present, the common methods in the field of BCa treatment include surgery, chemotherapy, radiotherapy, and combined immunotherapy, which have relative advantages and disadvantages and scope of application. According to the size, grade, and several tumors, different treatment schemes will be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that some nonmuscle BCa (NMIBC) is highly invasive, so it is necessary to apply local chemotherapy mode during treatment 9 . About 80% of BCa patients have reduced symptoms after intravesical chemotherapy, but the specificity of this method is not high 10 …”
Section: Introductionmentioning
confidence: 99%